The Effect of Financial Literacy and Financial Technology on the Sustainability of Micro and Small Enterprises in the Madura Region Through Financial Behavior as a Mediating Variable - Ririn Ariyanti S; Moh. Zaki Kurniawan (Universitas KH. Abdul Chalim Mojokerto, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital component of Indonesia's economic development. MSMEs not only drive economic growth but also absorb a large portion of the workforce. This study aims to examine the influence of Financial Literacy and Financial Technology on the sustainability of enterprises in the Madura region, with Financial Behavior as a mediating variable. MSMEs in Madura face challenges in financial management due to low Financial Literacy and limited access to Financial Technology, making business sustainability highly dependent on the Financial Behavior of entrepreneurs. This research employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), with data collected through purposive sampling from MSME actors in Madura. The results indicate that Financial Literacy and Financial Technology significantly affect Financial Behavior, which in turn has a positive impact on business sustainability. These findings suggest that improving literacy and utilizing Financial Technology are crucial for enhancing the Financial Behavior of MSME actors to support the sustainability of their businesses.